Internet, hiperfikcija i postmodernistička književnost - Hromadžić, Hajrudin (Monitor ISH, 2004)
The Internet, hyperfiction, and postmodern literature. The text addresses the type and distinctive features of hypertextual discourse, that is, the characteristics of its formation, or the organisation of hypertextual discourse units. From this point of view, three basic models of hypertextual discourse are defined: the World Wide Web or Internet as its most representative kind, where it is difficult to differentiate between the discourse units; hypertextual (interactive) fiction or hyperfiction (for example, Afternoon and WOE by Michael Joyce); and, finally, some examples of postmodern prose (by Borges, Calvino, Cortáyar, Pavić, and Robbe-Grillet).
Keywords: hipertekstualni diskurz; Internet; hiperfikcija; postmodernizem